Rituximab Treatment of Membranous Nephropathy after Failure of other Therapies- A Case report - Rista, Elvana; Cadri, Vilma; Duni, Anila; Musa, Juna; Hyseni, Fjolla; Guy, Ali; Khadra, Ronny; Idrizi, Alma (Archives of Clinical and Medical Case Reports, 2021)
Membranous Nephropathy (MN) also known as membranous glomerulonephritis is a slowly progressive kidney disease characterized of subepithelial immune complex deposits and subsequent thickening of glomerular basement membrane. MN is a common cause of proteinuria that may progress to ERDS. The decision to treat MN with immunosuppressive medications is complicated by the well-known natural history of disease and it depends on patient presentation and disease progression. Herein, we present a case of a 48-year-old male patient with weight gain, lower extremity edema, arterial hypertension, and nephrotic range proteinuria (13.5 gr). The patient was diagnosed with MN 14 years ago with relapses and remission of disease over the years. First immunotherapy was stared with cyclosporine and methylprednisolone, but the patient occurred to have cyclosporine-induced toxicity. Second immunotherapy was stared with methylprednisolone and cyclophosphamide that resulted in complete remission for 4 years. The disease relapsed again, and the patient was recommended the Rituximab treatment. Two doses of rituximab 1g were administered. In terms of total remission there was no indication for the third dose of rituximab.